POLICY OF ESTABLISHING THE DATE OF THE PAYMENT OF RURAL AND URBAN LAND AND BUILDING TAXES IN INDRAGIRI HILIR DISTRICT - Budi Suprianto (Jurnal Cendekia Hukum, 2022)
Payment of Land and Building Tax in the Rural and Urban Sector (PBB-P2) that exceeds the maturity limit will be subject to administrative sanctions in the form of interest of 2% per month calculated from a maximum period of 24 months from the time the tax becomes due. This could potentially lead to impartiality towards PBB P2 taxpayers who are late in paying taxes. This research is a type of normative legal research, which focuses on positive legal norms. This normative legal research method examines the law from an internal perspective with the object of research being legal norms. The purpose of the study was to analyze the setting of the due date for PBB-P2 payments and to analyze the legal concept of determining the due date for PBB-P2 payments. The results of the study explain that PBB-P2 through regional and central regulations does not provide administrative certainty in the payment and deposit of PBB-P2 and does not adjust the meaning of the tax year and can result in the obligation to pay PBB-P2 through the tax year. This will result in a lack of effectiveness in collecting PBB-P2 in the context of increasing local revenue. And it is necessary to harmonize existing regulations with the improvement of existing provisions and administration. This is important considering that local tax regulations and the tax itself are very important and of course adapted to the psychological, sociological and economic development of the community. Efforts to socialize the tax regulations made and the important thing is to urge taxpayers to fulfill their tax obligations clearly, correctly, on time and in the right amount.